Social interactions and aspirations formation in rural Ethiopia - Daniel Ayalew Mekonnen (University of Bonn, Center for Development Research (ZEF), 2016)
The recent literature postulates that aspirations are one of the key determinants of economic decision making, and that aspirations are formed socially through observations and by learning from 'relevant others' (or the 'reference group'). This study empirically examines the latter using survey data collected from sample households in rural Ethiopia. Specifically, the study examines the effect of social interactions on aspirations. Based on several definitions of a 'reference group', we find that aspirations are indeed socially determined through observations as well as social interactions. Results also indicate that the social network size is an important determinant of aspirations, attesting to the importance of widening the aspirations window - a person's cognitive world that shapes their aspirations. Across gender, results indicate that the effect of social interactions on aspirations is larger for females.
Keywords: D03; D62; Z1; 330; Social interactions; aspirations; Ethiopia